Identifying groundwater recharge connections in the Moscow (USA) sub-basin using isotopic tracers and a soil moisture routing model - Candel, Jasper (2016)
Globally, aquifers are suffering from large abstrac tions resulting in groundwater level declines. These declines can be caused by excessive abstraction for drinking water, irrigation purposes or industrial use. Basaltic aquifers also face these conflicts. A large flood basalt area (1.1 × 105 km2 ) can be found in the Northwest of the USA. This Columbia River Basalt Group (CRBG) consists of a thick series of basalt flows of Miocene age. The two major hydrogeological units (Wanapum and Grand Ronde formations) are widely used for water abstraction. The mean decline over recent decades has been 0.6 m year−1 . At present day, abstraction wells are drying up, and base flow of rivers is reduced. At the eastern part of CRBG, the Moscow sub-basin on the Idaho/ Washington State border can be found. Although a thick poor ly permeable clay layer exists on top of the basalt aquifer, groundwater level dynamics suggest that groundwater re charge occurs at certain locations. A set of wells and springs has been monitored bi-weekly for 9 months for δ18O and δ2 H. Large isotopic fluctuations and d-excess values close to the meteoric water line in some wells are indicating that recharge occurs at the granite/basalt interface through lateral flow paths in and below the clay. A soil moisture routing (SMR) model showed that most recharge occurs on the granitic mountains. The basaltic aquifer receives recharge from these sedimentary zones around the granite/basalt interface. The identification of these types of areas is of major importance for future managed-aquifer recharge solutions to solve problems of groundwater depletion.